Checklists for the Assessment of Correct Inhalation Therapy - Knipel, V.; Schwarz, S.; Magnet, F. S.; Storre, J. H.; Criée, C P; Windisch, W.; on behalf of the German Airway League (Pneumologie, 2017)
Introduction For the long-term treatment of obstructive lung diseases inhalation therapy with drugs being delivered directly to the lungs as an aerosol has become the method of choice. However, patient-related mistakes in inhalation techniques are frequent and recognized to be associated with reduced disease control. Since the assessment of patient-mistakes in inhalation has yet not been standardized, the present study was aimed at developing checklists for the assessment of correct inhalation. Methods Checklists were developed in German by an expert panel of pneumologists and professionally translated into English following back-translation procedures. The checklists comparably assessed three major steps of inhalation: 1) inhalation preparation, 2) inhalation routine, and 3) closure of inhalation.Results Checklists for eight frequently used inhalers were developed: Aerolizer, Breezhaler, Diskus (Accuhaler), metered-dose inhaler, Handihaler, Novolizer, Respimat, Turbohaler. Each checklist consists of ten items: three for inhalation preparation, six for inhalation routine, and one for closure of inhalation.Discussion Standardized checklists for frequently used inhalers are available in German and English. These checklists can be used for clinical routines or for clinical trials. All checklists can be downloaded free of charge for non-profit application from the homepage of the German Airway League (Deutsche Atemwegsliga e. V.): www.atemwegsliga.de.